2018
DOI: 10.1038/s41598-018-31978-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo functional characterisation of pheromone binding protein-1 in the silkmoth, Bombyx mori

Abstract: Male moths detect sex pheromones emitted by conspecific females with high sensitivity and specificity by the olfactory sensilla on their antennae. Pheromone binding proteins (PBPs) are highly enriched in the sensillum lymph of pheromone sensitive olfactory sensilla and are supposed to contribute to the sensitivity and selectivity of pheromone detection in moths. However, the functional role of PBPs in moth sex pheromone detection in vivo remains obscure. In the silkmoth, Bombyx mori, female moths emit bombykol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 41 publications
(46 reference statements)
3
30
0
Order By: Relevance
“…To test whether expression of olfactory system genes in the antennae were affected by loss of sex determination pathway genes, we quantified expression of genes that encode factors necessary for mate recognition by males, notably, pheromone binding proteins BmPBP1, BmPBP2, and BmPBP3 and odorant receptors BmOR1, BmOR2, and BmOR3 [45]. BmPBP1 binds to bombykol, and its dysfunction causes the failure of male courtship behavior [41]. Although BmPBP1 was expressed at wild-type levels in males mutant in Bmfru , it was significantly decreased in the males mutant in BmMasc , BmPSI , and Bmdsx .…”
Section: Resultsmentioning
confidence: 99%
“…To test whether expression of olfactory system genes in the antennae were affected by loss of sex determination pathway genes, we quantified expression of genes that encode factors necessary for mate recognition by males, notably, pheromone binding proteins BmPBP1, BmPBP2, and BmPBP3 and odorant receptors BmOR1, BmOR2, and BmOR3 [45]. BmPBP1 binds to bombykol, and its dysfunction causes the failure of male courtship behavior [41]. Although BmPBP1 was expressed at wild-type levels in males mutant in Bmfru , it was significantly decreased in the males mutant in BmMasc , BmPSI , and Bmdsx .…”
Section: Resultsmentioning
confidence: 99%
“…Many research reported at least one of the PBPs can well bind with sex pheromones [29][30][31] . In our analysis, PBP2 showed significantly male bias expression, and PBP1, PBP3…”
Section: Discussionmentioning
confidence: 99%
“…pathway genes, we quantified expression of genes that encode factors necessary for mate recognition by males, notably, pheromone binding proteins BmPBP1, BmPBP2, and BmPBP3 and odorant receptors BmOR1, BmOR2, and BmOR3 [45]. BmPBP1 binds to bombykol, and its dysfunction causes the failure of male courtship behavior [41]. Although BmPBP1 was expressed at wild-type levels in male mutants in Bmfru, it was significantly decreased in the males mutant in BmMasc, BmPSI, and Bmdsx.…”
Section: Expression Of Male-biased Olfactory System Genes Is Altered mentioning
confidence: 99%
“…The pheromone binding protein BmPBP1, which has a male-biased expression, is required for the selectivity of BmOR1 for bombykol [39]. Loss of function mutations in BmPBP1 or BmOR1 cause the disappearance of male sexual behavior [40,41]. Previous studies showed that the sex determination gene Bmdsx controls the expression of BmPBP1 and of BmOR1 [42,14].…”
Section: Introductionmentioning
confidence: 99%